2023
DOI: 10.3390/su15054111
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Motivations for Individual and Collective Sustainable Food Consumption: A Case Study of the Galician Conscious and Responsible Consumption Network

Abstract: Although consumer attitude towards sustainable food has increased over time, scientific research suggests that more profound comprehension is needed of the social and psychological dimensions that condition consumers’ willingness to purchase food items produced in a sustainable way. The current study attempts to understand the individual motivations that drive conscious consumption, in both the individual and collective spheres, expressed through joining a local social innovation in the food domain. A multi-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Through a multi-method design, which incorporated participatory observation, document analysis, and in-depth interviews with members of eight local food consumption initiatives in the Galician region of Spain, a study discovered motivations for sustainable food purchasing that included a desire to consume a healthy diet, pro-environmental and social values, environmental awareness, and feeling a connection to Galician rural areas. The study reported that motivations for participating in conscious consumption initiatives are influenced by basic needs (i.e., affordability and accessibility of organic, low-carbon, and fair-trade goods), sociopolitical goals, and social and psychological needs (e.g., connectedness, autonomy, and control over purchasing decisions) [34].…”
Section: Cultural Practice Theory and Sustainable Consumptionmentioning
confidence: 99%
“…Through a multi-method design, which incorporated participatory observation, document analysis, and in-depth interviews with members of eight local food consumption initiatives in the Galician region of Spain, a study discovered motivations for sustainable food purchasing that included a desire to consume a healthy diet, pro-environmental and social values, environmental awareness, and feeling a connection to Galician rural areas. The study reported that motivations for participating in conscious consumption initiatives are influenced by basic needs (i.e., affordability and accessibility of organic, low-carbon, and fair-trade goods), sociopolitical goals, and social and psychological needs (e.g., connectedness, autonomy, and control over purchasing decisions) [34].…”
Section: Cultural Practice Theory and Sustainable Consumptionmentioning
confidence: 99%
“…It is recognized that the cause of the global environmental crisis is people's resource-intensive lifestyles. As one of the most important factors of poor health and environmental degradation in the world, the food system is indicated, wherein, for example, the food sector is responsible for about 30% of the total energy consumption in the world and about 22% of total greenhouse gas emissions [Lema-Blanco et al, 2023]. Therefore, the fight against the environmental and social problems faced by humanity requires, above all, a change in the consumption system and raising consumer awareness, because their purchasing decisions are not only one of the causes for these problems, but also a way to solve them [Palacios-González et al, 2020].…”
Section: Responsible Consumption and The Usefulness Of Consumer Goods...mentioning
confidence: 99%